Carbon Credits: Who is the Leader of the Pack? - Medina, Vicente; Pardo, Angel; Pascual, Roberto (International Journal of Energy Economics and Policy, 2013)
We provide the first intraday analysis on the contribution to price discovery of two emissions carbon credits: European Union Allowances (EUAs) and Certified Emission Reductions (CERs). We find that EUAs lead price discovery but CERs play a growing role and, therefore, should not be ignored. Keywords: European Union Allowances; Certified Emission Reductions; co-integration, price-discovery; high frequency data; intraday analysis. JEL Classifications: G10